The gamer's brain : how neuroscience and UX can impact video game design - Hodent, Celia, ....- (Boca Raton : CRC Press, 2018)
At its core, UX is about understanding the gamer's brain: understanding human capabilities and limitations to anticipate how a game will be perceived, the emotions it will elicit, how players will interact with it, and how engaging the experience will be. This book is designed to equip readers of all levels, from student to professional, with cognitive science knowledge and user experience guidelines and methodologies. These insights will help readers identify the ingredients for successful and engaging video games, empowering them to develop their own unique game recipe more efficiently, while providing a better experience for their audience.
Keywords: Computer games; Human-computer interaction; Video games